Epoxy zinc-rich primer containing graphene-conductive nickel material and preparation method thereof

By using polyroxane crosslinked graphene nanosheets in epoxy zinc-rich primer to form a conductive network together with conductive nickel and zinc powder, the problem of poor dispersion of graphene materials in the coating is solved, and the corrosion resistance and mechanical properties of the coating are significantly improved.

CN117165149BActive Publication Date: 2025-04-11CHENGDU HONRE PAINT MAKING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311335239.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-11
Estimated Expiration
2043-10-16

AI Technical Summary

Technical Problem

The existing graphene materials have poor dispersion due to agglomeration in the coating, which affects the corrosion resistance, stability and strength of the coating.

Method used

The polyroxane crosslinked graphene nanosheets are used to form a conductive network with conductive nickel and zinc powder to form a conductive network with good connectivity. Through the synergistic action of mechanical interlocking network and dispersant, the dispersion and conductivity of graphene nanosheets are improved.

Benefits of technology

It significantly improves the corrosion resistance, stability and mechanical properties of the coating, forms a more uniform dispersion system and a conductive network with good connectivity, and enhances the corrosion protection of metal substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117165149B_ABST
    Figure CN117165149B_ABST
Patent Text Reader

Abstract

The invention discloses an epoxy zinc-rich primer containing a graphene-conductive nickel material and a preparation method thereof. The primer is composed of an A component and a B component, wherein the A component comprises the following components by weight percentage: 15-30% of an epoxy resin, 3-5% of a polyrotaxane cross-linked with graphene nanosheets, 7-15% of a conductive nickel powder, 40-55% of a zinc powder, 2-5% of a filler, 0.1-0.3% of a defoamer, 0.1-0.3% of an adhesion promoter, 0.2-0.5% of a fumed silica, 8-15% of a first organic solvent, 0.1-0.3% of a leveling agent, 0.2-0.5% of a dispersant, and 2-5% of an environmentally friendly zinc phosphate; and the B component comprises the following components by mass percentage: 40-60% of a curing agent; and 40-60% of a second organic solvent. The present invention utilizes PVA and HP‑α‑CD to form a mechanically interlocking polymer, which is cross-linked with graphene nanosheets to form a mechanically interlocking network; and utilizes the excellent dispersibility of polyrotaxane to make the graphene nanosheets form a uniform dispersion system in the resin, and cooperate with the conductive nickel and zinc powders to form a conductive network with good connectivity, which has a positive impact on improving the anti-corrosion performance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an epoxy zinc-rich primer containing a graphene-conductive nickel material and a preparation method thereof, belonging to the technical field of coatings. Background Art

[0002] The anti-corrosion mechanism of epoxy zinc-rich primer mainly comes from the following factors: 1. The sacrificial anode (Zn) protects the cathode (Fe) to form a conductive closed network; 2. When Zn is oxidized, non-conductive ZnO is generated, which is converted into barrier anti-corrosion; 3. Epoxy resin and polyamide curing agent form a dense protective film, which effectively blocks the invasion of corrosive media.

[0003] Research has found that adding graphene materials to epoxy zinc-rich paint can improve its anti-corrosion performance. Its main anti-corrosion mechanisms are as follows: 1. It has a good barrier effect. After adding graphene materials to paint products, they can be stacked up layer by layer in the paint to fill the gaps in the paint. After spraying, the bubbles and cracks inside the paint can no longer continue to expand, hindering the diffusion of corrosive media, thereby effectively slowing down the corrosion rate of the metal substrate. 2. It has a good hydrophobic effect. Since there is a large contact angle between graphene and water, it can have a good hydrophobic effect and can effectively prevent the passage of moisture, chloride ions and oxygen in the environment, thereby preventing the generation of oxidation reactions and achieving an anti-corrosion effect. 3. Reduce the rate of electrochemical corrosion. When the metal substrate sprayed with graphene paint is damaged, because graphene has conductive properties, it will quickly transfer the electrons lost by metal Fe to the surface of the paint, and the oxidation reaction will be transferred to the surface of the paint, effectively preventing OH - with Fe 3+ The chemical reaction between Fe 3+ The consumption of carbon dioxide is reduced, so the oxidation reaction is inhibited, thus achieving an anti-corrosion effect.

[0004] However, graphene materials are small in size and have a relatively small surface area, making them prone to aggregation. They will agglomerate in the coating, resulting in poor dispersion, making it impossible to form a well-connected conductive network in the coating, which has a negative impact on improving the anti-corrosion performance of the coating. The poor dispersion caused by the agglomeration phenomenon will also have a negative impact on improving the stability and strength of the coating. Summary of the invention

[0005] The purpose of the present invention is to provide an epoxy zinc-rich primer containing graphene-conductive nickel material and a preparation method thereof, so as to solve the problem that the existing graphene material has poor dispersibility due to the agglomeration phenomenon after being added to the coating, which is not conducive to improving the overall anti-corrosion performance, stability and strength of the coating.

[0006] The technical solution adopted by the present invention is:

[0007] An epoxy zinc-rich primer containing graphene conductive nickel material is composed of component A and component B, wherein component A comprises the following components in weight percentage: 15-30% of epoxy resin, 3-5% of polyrotaxane cross-linked with graphene nanosheets, 7-15% of conductive nickel powder, 40-55% of zinc powder, 2-5% of filler, 0.1-0.3% of defoamer, 0.1-0.3% of adhesion promoter, 0.2-0.5% of fumed silica, 8-15% of a first organic solvent, 0.1-0.3% of a leveling agent, 0.2-0.5% of a dispersant, and 2-5% of environmentally friendly zinc phosphate; and component B comprises the following components in mass percentage: 40-60% of a curing agent and 40-60% of a second organic solvent.

[0008] Preferably, the epoxy resin is selected from E51 epoxy resin and / or E44 epoxy resin; and the filler is selected from organic bentonite, montmorillonite, titanium dioxide or talc.

[0009] Preferably, the first organic solvent and the second organic solvent are selected from one or more of benzene solvents, ester solvents or alcohol solvents.

[0010] Preferably, the curing agent is an amine curing agent.

[0011] Preferably, the method for preparing the polyrotaxane cross-linked with graphene nanosheets comprises the following steps:

[0012] S1: Dissolve HP-α-CD in PBS buffer and then add PVA-NH 2 and stirring, the solution was placed at low temperature;

[0013] S2: Z-Gln-Gly and TGase are added to the solution and stirred; the mixture is dialyzed and freeze-dried;

[0014] S3: The freeze-dried product is dissolved in THF, centrifuged and dialyzed; the dialyzate is filtered and freeze-dried to obtain a polyrotaxane;

[0015] S4: placing graphene nanosheets in water to obtain a dispersion, then adding polyrotaxane to the graphene nanosheet dispersion to obtain a composite solution, vortexing, ultrasonicating, and degassing.

[0016] Preferably, in step S1, HP-α-CD and PVA-NH 2 The mass ratio is 1:(0.1-0.4).

[0017] Preferably, in step S2, the added amounts of Z-Gln-Gly and TGase are 5-9% and 1-3% of the mass of HP-α-CD, respectively.

[0018] Preferably, in step S3, the centrifugal speed is 3000-4000 rpm, the time is 15-20 min, and the centrifugation is performed 3-5 times.

[0019] Preferably, in step S4, in the composite solution, the concentration of the graphene nanosheet dispersion is 120-140 mg / ml, the mass fraction of the polyrotaxane is 16-22%; the vortex treatment is performed for 2-3 hours; and the ultrasonic treatment is performed for 6-10 minutes.

[0020] The method for preparing any of the above-mentioned epoxy zinc-rich primers containing graphene-conductive nickel material comprises the following steps:

[0021] Step 1, adding epoxy resin into the production tank;

[0022] Step 2, diluting the epoxy resin with the first organic solvent, slowly adding the dispersant and defoamer at a speed of 300-400 rpm, and stirring for 5-10 minutes;

[0023] Step 3, adding polyrotaxane cross-linked with graphene nanosheets, fumed silica, environmentally friendly zinc phosphate, and filler, stirring at 800-1000 rpm for 15-20 min; grinding the mixture to a fineness of 50 microns using a sand mill;

[0024] Step 4: slowly add the conductive nickel powder while stirring at 600-800 rpm, stir at 1000-1200 rpm for 20-30 min, and detect the fineness of 50 microns;

[0025] Step 5, slowly add zinc powder while stirring at 800-1000 rpm, and stir at 1000-1200 rpm for 20-30 min; test fineness 50 microns;

[0026] Step 6: Add adhesion promoter and leveling agent, stir at 800-1000 rpm for 5-10 min to obtain component A;

[0027] Step 7: The curing agent is mixed with the second organic solvent, and stirred at a speed of 600-800 rpm for 5-10 min to obtain component B.

[0028] The beneficial effects of the present invention are:

[0029] A mechanically interlocking polymer sliding-ring polyrotaxane is formed by using linear polymer PVA (polyvinyl alcohol) and multiple ring molecular hosts HP-α-CD (hydroxypropylated α-cyclodextrin). After the polyrotaxane is cross-linked with graphene nanosheets, a mechanically interlocking network is formed, and the graphene nanosheets are connected in series. The excellent dispersibility of the polyrotaxane is utilized to make the graphene nanosheets form a uniform dispersion system in the resin, and cooperate with the conductive nickel and zinc powders to form a conductive network with good connectivity, which has a positive effect on improving the anti-corrosion performance of the coating.

[0030] At the same time, the uniform dispersion of graphene nanosheets in the resin can increase the contact area with the resin (compared to agglomeration), can make full use of the antioxidant and UV resistance of the graphene nanosheets, and then can improve the stability of the coating; secondly, polyrotaxanes have very high mechanical strength, and graphene also has very high mechanical strength. Using polyrotaxanes to connect graphene nanosheets in series and disperse them in the system can improve the mechanical properties, wear resistance, strength and hardness of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is the SEM picture of the coating.

[0032] Figure 2 These are photos after the salt spray resistance test. DETAILED DESCRIPTION

[0033] The present invention will be specifically described below in conjunction with the accompanying drawings and embodiments.

[0034] The components used in the following examples and comparative examples are as follows:

[0035] E51 Epoxy Resin (128 Taiwan, China Nanya)

[0036] E44 epoxy resin (6101 Sanmu Chemical)

[0037] Titanium dioxide (NA100 Xuzhou titanium dioxide)

[0038] Dispersant (BYK163 BYK)

[0039] Defoaming agent (680 Digo)

[0040] Fumed Silica(N200 Haiyi Chemical)

[0041] Environmentally friendly zinc phosphate (MT601 Chongqing Maitu)

[0042] Zinc powder (600 mesh zinc Weiling)

[0043] Adhesion promoter (1051 Hemmings)

[0044] Conductive nickel powder (400 mesh Ningbo Jinlei)

[0045] Leveling agent (466 Hemings)

[0046] Amine modified curing agent (5625 Jiangsu Shisong)

[0047] Mixed solvent (xylene: trimethylbenzene: n-butanol = 4:2:2).

[0048] The corresponding substances in the following examples and comparative examples are as follows:

[0049] HP-α-CD (Hydroxypropylated α-cyclodextrin)

[0050] PBS buffer (phosphate buffered saline)

[0051] PVA-NH 2 (grafted with -NH 2 Polyvinyl alcohol, prepared by the method disclosed in the specification of CN 114377194 B)

[0052] Z-Gln-Gly(Z-Glutamylglycine)

[0053] TGase (transglutaminase)

[0054] THF (tetrahydrofuran).

[0055] The preparation method of the polyrotaxane (GPE-PRS) cross-linked with graphene nanosheets in the following examples and comparative examples is as follows:

[0056] Dissolve 10 g HP-α-CD in 40 ml PBS (0.1 mol / L -1 , pH 8) buffer, and then add 3g PVA-NH 2 and stirred to obtain a solution which was refrigerated at 3°C; 0.7 g of Z-Gln-Gly and 0.2 g of TGase were added to the solution and stirred at room temperature for 48 h; the mixture was then dialyzed to remove free HP-α-CD, Z-Gln-Gly and TGase; the dialyzed solution was freeze-dried; the resulting product was dissolved in 20 ml of THF, centrifuged at 3000 rpm for 15 min, centrifuged three times and then dialyzed for 36 h; the dialyzate was filtered through a 0.3 micron membrane and freeze-dried to obtain a polyrotaxane; 3 g of graphene nanosheets were placed in 25 ml of water to obtain a dispersion, and then 7 g of the polyrotaxane was added to the graphene nanosheet dispersion to obtain a composite solution, which was vortexed at room temperature for 2.5 h, ultrasonically treated for 10 min and degassed for subsequent use. Example 1

[0057] Component A

[0058]

[0059] Component B

[0060]

[0061] The preparation method of the epoxy zinc-rich primer containing graphene-conductive nickel material adopts the following steps: component A: adding epoxy resin into a production cylinder; diluting the epoxy resin with a mixed solvent, slowly adding a dispersant and a defoamer at a speed of 300-400rpm, and stirring for 5-10 minutes; adding polyrotaxane cross-linked with graphene nanosheets, fumed silica, environmentally friendly zinc phosphate, and titanium dioxide, and stirring at a speed of 800-1000rpm for 15-20 minutes; grinding the fineness to 50 microns with a sand mill; slowly adding conductive nickel powder while stirring at a speed of 600-800rpm, stirring at a speed of 1000-1200rpm for 20-30 minutes, and detecting the fineness of 50 microns; slowly adding zinc powder while stirring at a speed of 800-1000rpm, and stirring at a speed of 1000-1200rpm for 20-30 minutes; min, test fineness 50 microns; add adhesion promoter and leveling agent, stir at 800-1000rpm for 5-10min. Component B: Mix amine-modified curing agent with mixed solvent, stir at 600-800rpm for 5-10min. Example 2

[0062] Component A

[0063]

[0064] Component B

[0065]

[0066] The preparation method of the epoxy zinc-rich primer containing graphene-conductive nickel material adopts the following steps: component A: adding epoxy resin into a production cylinder; diluting the epoxy resin with a mixed solvent, slowly adding a dispersant and a defoamer at a speed of 300-400rpm, and stirring for 5-10 minutes; adding polyrotaxane cross-linked with graphene nanosheets, fumed silica, environmentally friendly zinc phosphate, and titanium dioxide, and stirring at a speed of 800-1000rpm for 15-20 minutes; grinding the fineness to 50 microns with a sand mill; slowly adding conductive nickel powder while stirring at a speed of 600-800rpm, stirring at a speed of 1000-1200rpm for 20-30 minutes, and detecting the fineness of 50 microns; slowly adding zinc powder while stirring at a speed of 800-1000rpm, and stirring at a speed of 1000-1200rpm for 20-30 minutes; min, test fineness 50 microns; add adhesion promoter and leveling agent, stir at 800-1000rpm for 5-10min. Component B: Mix amine-modified curing agent with mixed solvent, stir at 600-800rpm for 5-10min. Example 3

[0067] Component A

[0068]

[0069] Component B

[0070]

[0071] The preparation method of the epoxy zinc-rich primer containing graphene-conductive nickel material adopts the following steps: component A: adding epoxy resin into a production cylinder; diluting the epoxy resin with a mixed solvent, slowly adding a dispersant and a defoamer at a speed of 300-400rpm, and stirring for 5-10 minutes; adding polyrotaxane cross-linked with graphene nanosheets, fumed silica, environmentally friendly zinc phosphate, and titanium dioxide, and stirring at a speed of 800-1000rpm for 15-20 minutes; grinding the fineness to 50 microns with a sand mill; slowly adding conductive nickel powder while stirring at a speed of 600-800rpm, stirring at a speed of 1000-1200rpm for 20-30 minutes, and detecting the fineness of 50 microns; slowly adding zinc powder while stirring at a speed of 800-1000rpm, and stirring at a speed of 1000-1200rpm for 20-30 minutes; min, test fineness 50 microns; add adhesion promoter and leveling agent, stir at 800-1000rpm for 5-10min. Component B: Mix amine-modified curing agent with mixed solvent, stir at 600-800rpm for 5-10min.

[0072] Comparative Example 1

[0073] The difference from Example 1 is that what is added to component A is polyrotaxane (PRS) of uncrosslinked graphene nanosheets.

[0074] Component A

[0075]

[0076] Component B

[0077]

[0078] The preparation method of polyrotaxane (PRS) is as follows: 10 g HP-α-CD was dissolved in 40 ml PBS (0.1 mol / L -1 , pH 8) buffer, and then add 3g PVA-NH 2 and stirring, and the obtained solution was refrigerated at 3°C; 0.7 g Z-Gln-Gly and 0.2 g TGase were added to the solution and stirred at room temperature for 48 h; the mixture was then dialyzed to remove free HP-α-CD, Z-Gln-Gly and TGase; the dialyzed solution was freeze-dried; the obtained product was dissolved in 20 ml THF, centrifuged at 3000 rpm for 15 min, centrifuged 3 times and then dialyzed for 36 h; the dialyzate was filtered through a 0.3 micron membrane and freeze-dried.

[0079] The preparation method of epoxy zinc-rich primer containing graphene-conductive nickel material adopts the following steps: component A: adding epoxy resin into a production cylinder; diluting the epoxy resin with a mixed solvent, slowly adding a dispersant and a defoamer at a speed of 300-400rpm, and stirring for 5-10 minutes; adding polyrotaxane, fumed silica, environmentally friendly zinc phosphate, and titanium dioxide, and stirring at a speed of 800-1000rpm for 15-20 minutes; grinding the fineness to 50 microns with a sand mill; slowly adding conductive nickel powder while stirring at a speed of 600-800rpm, stirring at a speed of 1000-1200rpm for 20-30 minutes, and detecting the fineness of 50 microns; slowly adding zinc powder while stirring at a speed of 800-1000rpm, and stirring at a speed of 1000-1200rpm for 20-30 minutes; min, test fineness 50 microns; add adhesion promoter and leveling agent, stir at 800-1000rpm for 5-10min. Component B: Mix amine-modified curing agent with mixed solvent, stir at 600-800rpm for 5-10min.

[0080] Comparative Example 2

[0081] The difference from Example 1 is that single graphene nanosheets (GPE) are added to component A.

[0082] Component A

[0083]

[0084] Component B

[0085]

[0086] The preparation method of epoxy zinc-rich primer containing graphene-conductive nickel material adopts the following steps: component A: adding epoxy resin into a production cylinder; using a mixed solvent to dilute the epoxy resin, slowly adding a dispersant and a defoamer at a speed of 300-400rpm, and stirring for 5-10 minutes; adding graphene nanosheets, fumed silica, environmentally friendly zinc phosphate, and titanium dioxide, stirring at a speed of 800-1000rpm for 15-20 minutes; using a sand mill to grind the fineness to 50 microns; slowly adding conductive nickel powder while stirring at a speed of 600-800rpm, stirring at a speed of 1000-1200rpm for 20-30 minutes, and detecting the fineness of 50 microns; slowly adding zinc powder while stirring at a speed of 800-1000rpm, and stirring at a speed of 1000-1200rpm for 20-30 minutes; min, test fineness 50 microns; add adhesion promoter and leveling agent, stir at 800-1000rpm for 5-10min. Component B: Mix amine-modified curing agent with mixed solvent, stir at 600-800rpm for 5-10min.

[0087] SEM characterization

[0088] from Figure 1 (The left side is the SEM photo of the coating obtained from the components in Example 1, and the right side is the SEM photo of the coating obtained from the components in Comparative Example 2) It can be seen that the coating prepared in Example 1 has relatively better uniformity and density between ions, indicating that the graphene nanosheets, conductive nickel powder and zinc powder are more evenly dispersed and can achieve close overlap with each other.

[0089] Coating Testing

[0090] Dry plate realization: Component A: Component B = 5:1 ratio, use mixed solvent to adjust viscosity, spray viscosity is adjusted to 30-40S (apply 4 cups). Spray the plate and test the physical properties. The physical property dry plate is placed in a 25℃ constant temperature box to dry for 48 hours to test the conventional performance. After 7 days of type inspection, the salt spray resistance, surface resistance, and chemical resistance test are tested. The conventional inspection thickness is controlled at 20-30µm, and the type inspection thickness is controlled at 80-100µm.

[0091] Testing basis: Fineness is in accordance with GB / T6753.1; drying is in accordance with GB / T1728; thickness is in accordance with GB / T13452.2; bendability is in accordance with GB / T6742; impact resistance is in accordance with GB / T1732; cross-cutting test is in accordance with GB / T9286; chemical resistance is in accordance with GB / T9274; high and low temperature cycle test is in accordance with Note 1; surface resistivity is in accordance with GB1410; neutral salt spray resistance is in accordance with GB / T1771.

[0092] The results are as follows:

[0093] Table 1 Dry plate properties of primers obtained in Examples 1-3 and Comparative Examples 1-2

[0094]

[0095] Note 1: High and low temperature cycle test conditions: 80±2℃, 95%RH 4h, 80℃ to -40℃ 2h (temperature change rate 1℃ / min), -40±2℃ 4h, -40℃ to 80℃, 95%RH 2h (temperature change rate 1℃ / min), 12h as one cycle, the sample should be placed at room temperature for more than 16h after the 60-cycle test is completed before testing; when the coating thickness is ≤300µm, the cross-cut test is carried out, when the thickness is ≤80µm, the cross-cut spacing is 1mm, when the thickness is 80-150µm, the cross-cut spacing is 2mm, when the thickness is 150-300µm, the cross-cut spacing is 3mm, when the coating thickness is >300µm, the X-cut test is carried out, and the adhesion is not less than level 3.

[0096] like Figure 2 As shown, at 4200h of the test, the surface photographs of the coatings in Example 1 and Control Examples 1 and 2 show that the surface of the coating in Example 1 is basically normal, while the coatings prepared in Control Examples 1 and 2 show obvious rust, indicating that the coatings have poor corrosion resistance.

[0097] From the dry plate performance test results in Table 1, it can be seen that the epoxy zinc-containing primer with graphene-conductive nickel has significantly improved comprehensive performance compared with the standard 80% national standard requirements, and is superior to the comparative example in terms of salt spray resistance, impact resistance, resistance to cold and hot cycles, surface resistivity, etc. It can be seen from the comparison of salt spray resistance that, compared with the comparative example 1, the addition of graphene nanosheets to the epoxy zinc-rich primer in Example 1 can improve the anti-corrosion performance of the coating; at the same time, it can be seen from Example 1 and the comparative example 2 that the linear polymer PVA (polyvinyl alcohol) and multiple ring molecular bodies HP-α-CD (hydroxypropylated α-cyclodextrin) are used to form a mechanical interlocking polymer, which is cross-linked with the graphene nanosheets to form a mechanical interlocking network, and the graphene nanosheets are connected in series, so that the coating can form a more uniform dispersion system, and the more uniform dispersion system makes the synergistic effect between the graphene nanosheets, the conductive nickel, and the zinc powder better, so as to form a conductive network with better connectivity, which has a positive effect on improving the anti-corrosion performance of the coating. This product can be used in military stealth, electronic shielding, marine anti-corrosion, bridge anti-corrosion, water conservancy and hydropower anti-corrosion, wind power generation and other fields.

[0098] At the same time, the uniform dispersion of graphene nanosheets in the resin can increase the contact area with the resin (compared to agglomeration), can make full use of the antioxidant and UV resistance of the graphene nanosheets, and then can improve the stability of the coating; secondly, polyrotaxanes have very high mechanical strength, and graphene also has very high mechanical strength. Using polyrotaxanes to connect graphene nanosheets in series and disperse them in the system can improve the mechanical properties, wear resistance, strength and hardness of the coating.

[0099] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. An epoxy zinc-rich primer containing graphene-conductive nickel material, which is composed of component A and component B, and is characterized in that: The component A comprises the following components in weight percentage: 15-30% epoxy resin, 3-5% polyrotaxane cross-linked with graphene nanosheets, 7-15% conductive nickel powder, 40-55% zinc powder, 2-5% filler, 0.1-0.3% defoamer, 0.1-0.3% adhesion promoter, 0.2-0.5% fumed silica, 8-15% first organic solvent, 0.1-0.3% leveling agent, 0.2-0.5% dispersant, and 2-5% environmentally friendly zinc phosphate; The filler is selected from organic bentonite, montmorillonite, titanium dioxide or talc; The method for preparing the polyrotaxane cross-linked with graphene nanosheets comprises the following steps: S1: Dissolve HP-α-CD in PBS buffer, then add PVA-NH2 and stir, and place the solution at low temperature, wherein the mass ratio of HP-α-CD to PVA-NH2 is 1:(0.1-0.4); S2: adding Z-Gln-Gly and TGase into the solution and stirring; dialyzing the mixture and freeze-drying it; wherein the amount of Z-Gln-Gly and TGase added is 5-9% and 1-3% of the mass of HP-α-CD, respectively; S3: The freeze-dried product is dissolved in THF, centrifuged and dialyzed; the dialyzate is filtered and freeze-dried to obtain a polyrotaxane; S4: placing graphene nanosheets in water to obtain a dispersion, then adding polyrotaxane to the graphene nanosheet dispersion to obtain a composite solution, vortexing, ultrasonicating, and degassing; The B component includes the following components by mass percentage: 40-60% of a curing agent; and 40-60% of a second organic solvent.

2. The epoxy zinc-rich primer containing graphene-conductive nickel material according to claim 1, characterized in that: The epoxy resin is selected from E51 epoxy resin and / or E44 epoxy resin.

3. The epoxy zinc-rich primer containing graphene-conductive nickel material according to claim 1, characterized in that: The first organic solvent and the second organic solvent are selected from one or more of benzene solvents, ester solvents or alcohol solvents.

4. The epoxy zinc-rich primer containing graphene-conductive nickel material according to claim 1, characterized in that: The curing agent is an amine curing agent.

5. The epoxy zinc-rich primer containing graphene-conductive nickel material according to claim 1, characterized in that: In step S3, the centrifugal speed is 3000-4000 rpm, the time is 15-20 min, and the centrifugation is performed 3-5 times.

6. The epoxy zinc-rich primer containing graphene-conductive nickel material according to claim 1, characterized in that: In the step S4, in the composite solution, the concentration of the graphene nanosheet dispersion is 120-140 mg / mL, the mass fraction of the polyrotaxane is 16-22%; the vortex treatment is performed for 2-3 hours; and the ultrasonic treatment is performed for 6-10 minutes.

7. The method for preparing the epoxy zinc-rich primer containing graphene-conductive nickel material according to any one of claims 1 to 6, characterized in that: The steps include: Step 1, adding epoxy resin into the production tank; Step 2, diluting the epoxy resin with the first organic solvent, slowly adding the dispersant and defoamer at a speed of 300-400 rpm, and stirring for 5-10 minutes; Step 3, adding polyrotaxane cross-linked with graphene nanosheets, fumed silica, environmentally friendly zinc phosphate, and filler, stirring at 800-1000 rpm for 15-20 min; grinding the mixture to a fineness of 50 microns using a sand mill; Step 4: slowly add the conductive nickel powder while stirring at 600-800 rpm, stir at 1000-1200 rpm for 20-30 min, and detect the fineness of 50 microns; Step 5, slowly add zinc powder while stirring at 800-1000 rpm, stir at 1000-1200 rpm for 20-30 min, and detect the fineness of 50 microns; Step 6: Add adhesion promoter and leveling agent, stir at 800-1000 rpm for 5-10 min to obtain component A; Step 7: The curing agent is mixed with the second organic solvent, and stirred at a speed of 600-800 rpm for 5-10 min to obtain component B.

Citation Information

Patent Citations

  • A bandage or dressing for the prevention and / or treatment of skin injuries and its application.

    CN114377194B

  • All-cyclodextrin poly-rotaxane and preparation method thereof

    CN101775146A

  • Modified polyrotaxane, medicine carrier micelle based on polyrotaxane and preparation method and application of micelle

    CN108395543A